Analisis Corrected Count Increment (CCI) pada penderita post transfusi trombosit apheresis di RSUP Dr. Wahidin Sudirohusodo, Makassar, Indonesia - Lisdiana Amin Asri; Sri Juliani; Rachmawati Muhiddin (Intisari Sains Medis, 2019)
Background: Platelet refractoriness is a problem in the implementation of platelet transfusion. It is a lack of increased platelets after platelet transfusion. This study aimed to analyze the increase in platelet counts of patients who received apheresis platelet transfusion by using Corrected Count Increment (CCI) formula at Dr. Wahidin Sudirohusodo General Hospital Makassar.Methods: This was an observational cross sectional study with 242 thrombocytopenia patients. The success of platelet transfusion was calculated using the CCI formula with CCI values after transfusion of 4.5 x 109/L at 24 hours post transfusion. Statistical analysis used chi square, t-independent, and spearmen’s correlation test, with significant test results if p-value was < 0.05.Results: An average increase of platelet counts was 28.5 x 109/L. Successful thrombocyte transfusion was found in 107 subjects (44.2%) and unsuccessful in 135 subjects (55.8%). The proportion of successful transfusion was found to be higher in men (45.5%) than women (43.2%), however, it was not significant (p > 0.05). There was a significant relationship between young age and successful thrombocyte transfusion (p < 0.001). Unsuccessful transfusion rate was high in cases of malignancy, infection, bleeding, and metabolic disease (p < 0.05).Conclusions: There was a significant negative correlation between age and CCI, older age presented lower value of CCI. Characteristics of disease affected the successful of apheresis thrombocyte transfusion.